'Normal weight' is really not normal in chronic disease . (27th August 2022) - Anker, Stefan D; Usman, Muhammad Shariq; Butler, Javed
Graphical Abstract: Graphical Abstract Risk of (all-cause) mortality and worsening heart failure events vs. body mass (BMI) index at baseline in the DELIVER trial. Blue and red lines represent approximations of relative risk vs. BMI from the data presented. 4